2020
DOI: 10.2337/dc20-2604
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Effect of Two Weeks of Dapagliflozin Treatment in Patients With Type 2 Diabetes and Preserved Kidney Function During Standardized Sodium Intake: Results of the DAPASALT Trial

Abstract: OBJECTIVE Sodium–glucose cotransporter 2 (SGLT2) inhibitors reduce the risk for heart failure hospitalization potentially by inducing sodium excretion, osmotic diuresis, and plasma volume contraction. Few studies have investigated this hypothesis, but none have assessed cumulative sodium excretion with SGLT2 inhibition during standardized sodium intake in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS The DAPASALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 38 publications
7
71
0
2
Order By: Relevance
“…It is also of interest that dapagliflozin did not induce a significant diuretic effect, as reflected in 24-h urinary volumes. The lack of persistent natriuretic and diuretic effects of SGLT2 inhibitors has been documented before, 4,10 including in a study with controlled sodium intake, 11 There is also the possibility that patients consumed less salt after 12 weeks of treatment because of the new sodium balance achieved.…”
Section: *# *#mentioning
confidence: 90%
See 1 more Smart Citation
“…It is also of interest that dapagliflozin did not induce a significant diuretic effect, as reflected in 24-h urinary volumes. The lack of persistent natriuretic and diuretic effects of SGLT2 inhibitors has been documented before, 4,10 including in a study with controlled sodium intake, 11 There is also the possibility that patients consumed less salt after 12 weeks of treatment because of the new sodium balance achieved.…”
Section: *# *#mentioning
confidence: 90%
“…SGLT2 inhibitors also induce natriuresis by inhibiting transport of one sodium ion for every molecule of glucose excreted. However, this effect is also transient, owing to compensatory mechanisms that increase sodium reabsorption at other nephron sites 3–6 . Clearly, therefore, we have to investigate other avenues to explain the antihypertensive action of these drugs, which might contribute to the beneficial effects of these drugs on cardiovascular outcomes.…”
mentioning
confidence: 99%
“…Activation of tubuloglomerular feedback is a result of SGLT2 inhibitor ability to block sodium and glucose reabsorption in the proximal tubules resulting in a modest diuresis 26,27 . Glucosuria is sustained and appears to account for the increase in urine volume observed, whereas natriuresis is inconsistently observed and when present is modest and unsustained 28–30 . The reduction in plasma volume and resultant hemoconcentration have been suggested to be the most important mediator of CV risk reduction seen in the EMPA‐REG OUTCOME trial 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The lower blood pressure was not accompanied by natriuresis but was associated with increased renal expression of HIF-1α and the amelioration of renal inflammation. The recent DAPASALT trial also reported that dapagliflozin produced no significant natriuresis in association with its blood pressure lowering effect [125], which is compatible with the roles of inflammation, oxidative stress, and vascular dysfunction in hypertension [126]. In a rat model of angiotensin IIdependent hypertension, on the other hand, empagliflozin did not affect blood pressure but did prevent the development of renal glomerulosclerosis, tubulointerstitial fibrosis, an increase in inflammatory infiltrates, and the expression of collagen types I and IV [127].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%